Dampak Keseimbangan Air terhadap Pertumbuhan Tanaman Kelapa Sawit (Elaeis guineensis): Review Literature - Barokah, Mantep; Dewi, Ferra Listya Sandra; Rahmawati, Aulia (Agritechpedia, 2024)
The oil palm plant, which has the Latin name Elaeis guineensis jacq, is a plant that comes from the Arecaceae family or the annual plant family. Oil palm is a prospective plantation commodity for cultivation. Oil palm plantations in Indonesia are spread across the islands of Sumatra, Sulawesi, and Kalimantan. Oil palm is a plant that is prone to drought stress, because it has a shallow root system. Water storage in oil palms is not as much as in other crops given their shallow-rooted morphology. Water carried during the rainy season escapes into the soil layer below the root zone so that water is not retained even though oil palms are cultivated on flat land. Even with good drainage, a lot of water still escapes. Water becomes unbalanced for plant growth. Oil palms have no water reserves during the dry season. This becomes a problem if oil palms experience drought stress. Water stress can be seen from changes in plant morphology and physiology